Development and Validation of an Evaluation Instrument for the Industrial Field Practice Program in Informatics Engineering at Universitas Putra Indonesia YPTK Padang - Renny Permata Saputri; Fahmi Rijal; Muhammad Giatman; Ambiyar Ambiyar; Krismadinata Krismadinata; Nurhasan Syah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Industrial Field Practice (PLI) is essential in vocational education, bridging academic learning with real-world industry experience. However, evaluating its effectiveness often lacks standardized and validated instruments, particularly in Informatics Engineering programs. This study aims to develop and validate an evaluation instrument for the PLI Program at Universitas Putra Indonesia YPTK Padang. The instrument was constructed using Stake’s Countenance Evaluation Model, which includes three components: antecedents, transactions, and outcomes. A total of 80 items were initially developed through literature review and expert consultation. Content validation was conducted using the Aiken’s V formula, involving three experts in vocational education evaluation. Items with V 0.8 were considered valid. Of the 80 items developed, 70 met the content validity criteria and were deemed valid, while 10 required revision based on expert feedback. Valid items measured aspects such as student readiness, supervision quality, task relevance, use of technology, work ethics, technical skills, soft skills, and final project outcomes. Each item was aligned with industrial expectations and educational standards. The results demonstrate that the developed instrument has strong content validity and provides a comprehensive framework for evaluating PLI implementation. It supports quality assurance and continuous improvement in vocational education. The instrument can be adapted by other institutions for similar programs in different fields.